2017
DOI: 10.3390/ani7020010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Deck Level, Body Surface Temperature and Carcass Damages in Italian Heavy Pigs after Short Journeys at Different Unloading Environmental Conditions

Abstract: Simple SummaryTransport duration and thermal conditions can negatively affect pig welfare and carcass quality. The effects of short journeys (30 min) in different thermal-humidity conditions on the body surface temperature of live heavy pigs and carcass skin damage were examined. Body temperature increased with increasing Temperature Humidity Index (THI) class. The highest and lowest body surface temperatures were found in pigs located on the middle and upper decks, respectively. THI class significantly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
2
14
2
2
Order By: Relevance
“…Moreover, pigs located in the front and rear compartments or in the upper and lower decks have an increased number of carcass skin bruises and a reduced pork quality [43]. A tendency towards higher skin damage scores was found in pigs transported on the trailer compared with those located on the lorry because the trailer is subjected to more vibrations and movements than the lorry [9]. The fact that we only analysed samples of pigs travelling in the trailer may have therefore affected our results to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pigs located in the front and rear compartments or in the upper and lower decks have an increased number of carcass skin bruises and a reduced pork quality [43]. A tendency towards higher skin damage scores was found in pigs transported on the trailer compared with those located on the lorry because the trailer is subjected to more vibrations and movements than the lorry [9]. The fact that we only analysed samples of pigs travelling in the trailer may have therefore affected our results to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…For long journeys additional requirements are included, i.e., roof, floor and bedding, feed, water supply, ventilation and temperature monitoring, and a navigation system. In addition, regardless of journey duration, the position of the animals in the vehicle during transport can affect skin blemishes and meat quality [8,9]. Indeed, the truck deck affects animal stress levels in a highly variable way [10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the Canadian Food Inspection Agency carried out a survey of 22 slaughterhouses and 13 auction markets and assembly facilities across Canada over the period of 2 months involving a total of 3, 433, 823 boars (hogs) and sows and the data showed that 4, 684 (0.14%) pigs were non-ambulatory at the time of arrival at the slaughterhouse. During transport, 1,372 pigs became non-ambulatory (Appelt, 2003;Canada Gazette, 2004). More importantly, carcasses of 60% of non-ambulatory pigs arriving at slaughterhouses were partially or fully condemned.…”
Section: Emergency Slaughtermentioning
confidence: 99%
“…This creates perspectives to determine meat quality automatically in the slaughter line, by measuring carcass temperature via a temperature probe. Another possibility is measuring surface temperature using infrared thermography of live animals just before slaughter [87,88]. However, based on the low to moderate correlations with other physiological indicators, infrared thermography cannot be used as a stand-alone measurement of the physiological condition of pigs in response to stress [87].…”
Section: Carcass Temperaturementioning
confidence: 99%